PENYULUHAN PENINGKATAN MINAT WIRAUSAHA MELALUI ASPEK SOSIAL DAN BUDAYA PADA MASYARAKAT YANG TERDAMPAK COVID-19 DI KELURAHAN BUNGKUTOKO KECAMATAN NAMBO KOTA KENDARI - Nurwati; Husin; Alida Palilati (Bajang Institute, 2022)
The purpose of this training is to provide an understanding to the people of Bungkutoko Village, Nambo District, Kendari City in order to understand the importance of increasing interest in Entrepreneurship through social and cultural aspects in increasing household income towards economic independence and increasing income for the community. The method used in the training is the lecture method (direction). and explanation simultaneously to the community. The method of discussion and question and answer was also carried out after the lecture (direction/explanation) was given on the importance of increasing interest in Entrepreneurship through social and cultural aspects in increasing household income towards economic independence and increasing income for the people of Bungkutoko Village, Nambo District, Kendari City, Southeast Sulawesi.